A Deep Dive Into Instagram's Top Skinfluencers - Hadley Johnson; Claire Herzog; Rob L Shaver; Sara A Hylwa (JMIR Publications, 2023)
We characterized skinfluencers from various training backgrounds and compared their posts on Instagram featuring skin care products.